2018
DOI: 10.1007/s00181-018-1562-0
|View full text |Cite
|
Sign up to set email alerts
|

Applying panel vector autoregression to institutions, human capital, and output

Abstract: We bridge two areas of study by applying panel vector autoregression (PVAR) to human capital, political institutions, economic institutions, and economic output per capita. Institutions and human capital have competed within the scholarly literature as hypotheses explaining the origins of economic growth. Elsewhere, our measure of economic institutions, the Economic Freedom of the World index, has recently been explored extensively as a dependent variable, whereas previously it had been used as an explanatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…Aixalá and Fabro () ran a Granger causality model with economic growth/investment and economic freedom (both levels and changes) finding bi‐directional causality. This was consistent with the findings of Farr, Lord, and Wolfenbarger (), Murphy and O'Reilly (Forthcoming), and Góes ().…”
Section: The Determinants Of Economic Freedomsupporting
confidence: 92%
“…Aixalá and Fabro () ran a Granger causality model with economic growth/investment and economic freedom (both levels and changes) finding bi‐directional causality. This was consistent with the findings of Farr, Lord, and Wolfenbarger (), Murphy and O'Reilly (Forthcoming), and Góes ().…”
Section: The Determinants Of Economic Freedomsupporting
confidence: 92%
“…Organizations such as the Fraser Institute annually publish indexes of economic freedom, distinguishing aspects such as low government spending, protection of property rights, sound money, free trade, and low regulatory stringency. Various studies have argued that free markets and competition stimulate income per capita or economic growth and have found a positive relationship (De Haan et al 2006;Justesen 2008;Graafland and Compen 2015;Faria et al 2016;Murphy 2016;Murphy and O'Reilly 2018;Spruk and Kešeljević 2018). Other studies have argued that economic freedom stimulates life satisfaction and have shown that a positive relationship exists between them (Veenhoven 2000;Ovaska and Takashima 2006;Gropper et al 2011;Gehring 2013;Graafland and Compen 2015) as well as with (several dimensions of) emotional well being .…”
Section: Well-being and Economic Freedommentioning
confidence: 99%
“…The concept has been analyzed in more than 400 scientific articles (Hall and Lawson 2014). Previous research has shown that economic freedom is positively related to income per capita or economic growth (De Haan et al 2006;Justesen 2008;Faria et al 2016;Murphy 2016;Murphy and O'Reilly 2018;Spruk and Kešeljević 2018). Other studies have shown 1 3 that economic freedom also correlates with life satisfaction (Veenhoven 2000;Ovaska and Takashima 2006;Gropper et al 2011;Graafland and Compen 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Stocker (2016) looks at a variety of kinds of crises and determines that banking, domestic debt and inflation crises weaken economic freedom, while external debt crises may weakly increase it. Murphy and Smith (2018) find that aggregate demand shortfalls, as defined by declines in Nominal Gross Domestic Product, foreshadow declines in economic freedom for a period but not over the very long run. Most recently, Bjornskov and Rode (forthcoming) find an interaction between growth crises (five-year periods over which growth is negative) and government ideology, such that left-wing governments will increase the size of government and regulation when confronted with a crisis.…”
Section: Introductionmentioning
confidence: 84%